Qualidade da água e deposição de sedimentos em trechos da bacia hidrográfica do rio Pirapó representados pelo ribeirão Maringá - Schneider, Roselene Maria (2009)
This thesis aimed to develop and apply methodologies for assessing and monitoring some processes that occur in the Pirapó river basin, using environmental diagnostics as a way of supporting actions to planning and management of Pirapó river basin. Monitoring water quality, sediment transport and bank erosion were used for the environmental assessment of the Maringá stream. The results of water quality monitoring show that the water ambient for the Pirapó river is polluted. It was also observed that the effects generated by man-made urban presence are the most significant in terms of reducing water quality, especially the sewers. The sediment transport varied in relation to the flow, giving an increase performance of transport with increased flow, indicating that the generation of sediment is related to the rains that occur in the basin. In addition, the study showed that the amount of sediment transport at Maringá watershed is low in medium and low flows in comparison with other watercourses. The study of bank erosion showed that the losses are significant and have connection with the high flow generated, since, upon the occurrence of these, significant loss of mass were observed.